الحداثيون العرب والقرآن الكريم: نصر حامد أبو زيد أنموذجاً دراسة في المناهج والأساليب: Arab Modernist and the Holy Quran: A study of Methodology and style of Nasr Hamid Abu Zayd - نصيرات صالح محمد (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2012)
تهدذ هذه الدراسة إلى الحفر على الأصول النظرية والفلسفية التي تحكم توجهات العلمانيين الحداثيين؛ كما يمثلهم نصر حامد أبو زيد، عن طريق البحث في الأدوات والمناهج التي يستعملها في كتاباته عن القرآن الكريم. وتستخدم الدراسة المنهج الاستقرائي القائم على القراءة النقدية، والمقارنة، والخلوص إلى النتائج من خلال اختبار الفرضيات التي هي أساس هذه الدراسة. وجدت الدراسة أن نصر حامد أبو زيد في تعامله مع القرآن الكريم يلجأ إلى التدليس، وإخفاء الحقائق أو إخراجها عن سياقها. وقد توصّلت الدراسة كذلك إلى أنّ ما يقوله هؤلاء لا جديد فيه غالباً؛ فهو تكرار لما قاله المستشرقون الذين قالوا عمّا كتبه تلاميذهم "هذه بضاعتنا رُدّت إلينا". This article aims at investigating the theoretical and philosophical foundations of Arab secular modernists, as represented by the Nasr Hamid Abu Zayd, through investigating the methodology and style he used in his works. The article uses the inductive approach based on the critical reading, comparison and testing hypotheses. In his study of the Holy Quran, the article found out that Abu Zayd uses misleading methods, hides or denies the truth, and decontextualizes texts. The study concludes that Arab Modernists in general did not bring anything new. There studies have been a repetition of Orientalists’ methodology. These Orientalists in fact have described their students from Arab modernist as those “who bring back what they have already taken from us”.